AB0819 Indirect Comparison of Urate-Lowering Therapies for Hyperuricemic Patients with or without Gout: Meta-Analysis of Randomized Controlled Trials. (15th July 2016) - Fan, M.; Liu, J.; Zhao, B.; Wu, X.; Gu, J.
Abstract : Background: Hyperuricemia is the most significant risk factor for the development of gout, defined as a serum concentration of uric acid at 6.8 mg/dl or greater. Long-term maintenance of serum urate levels below its saturation threshold can reduce the frequency of acute gout flares and resolve the existing tophi. Objectives: To assess the urate-lowering efficacy and safety of febuxostat, allopurinol and benzbromarone in hyperuricemic patients with or without gout. Methods: We included all the randomized controlled trials (RCTs) that compared any urate-lowering medication with placebo or head to head. The efficacy outcomes included the proportions of achieving the target urate level (<6.0 mg/dl) at final visit or last 3 visits and the percentage of gout flares during the first 8 weeks. The safety outcomes included total adverse events (AEs), withdrawals due to AEs and serious AEs. A Bayesian network model was used to compare all interventions simultaneously. Results: Sixteen RCTs (6645 patients) were included in the analysis. All urate-lowering therapies were more likely to achieve the target urate level at final visit and last 3 visits than placebo, but had an inconclusive higher risk of gout flares. Furthermore, all of the febuxostat doses (40, 80, 120, 240 mg/day) had a higher proportion of achieving the target urate level at final visit than allopurinol. With febuxostat dosages increased, more patients achieved the target urate level. Febuxostat 240 mg/day was the most effective drug for serum urate normalization. Regarding safety, there were no significant differences among urate-lowering therapies and placebo for total AEs, withdrawals due to AEs and serious AEs, except that allopurinol had a higher risk of total AEs than febuxostat 120mg/day. Conclusions: Compared to placebo, all urate-lowering therapies are effective in achieving the target urate level for hyperuricemic patients. Febuxostat is more efficacious than allopurinol for serum urate normalization. References: Hamburger M, Baraf HS, Adamson TC, 3rd, et al. 2011 recommendations for the diagnosis and management of gout and hyperuricemia. The Physician and sportsmedicine 2011;39(4):98–123. Khanna D, Fitzgerald JD, Khanna PP, et al. 2012 American College of Rheumatology guidelines for management of gout. Part 1: systematic nonpharmacologic and pharmacologic therapeutic approaches to hyperuricemia. Arthritis care & research 2012;64(10):1431–46. Perez-Ruiz F, Liote F. Lowering serum uric acid levels: what is the optimal target for improving clinical outcomes in gout? Arthritis and rheumatism 2007;57(7):1324–8. Disclosure of Interest: None declared